The level of death anxiety among a sample of individuals who survived the earthquake disaster (February 6 in Syria) A field study in Latakia Governorate - غانم لينا; ريما سعدي; سام صقور (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The study aimed to know the level of death anxiety among the survivors of the people who struck Syria on (February 6, 2023), and who were displaced from their homes to come to the monkey shelter center in Latakia Governorate. It also aimed to study the differences in death anxiety among members of the diverse sample. (marital status, gender) Study hypotheses: The Templer (1967) death anxiety scale was applied, consisting of (15) items to be answered (yes, no), and it was applied to a group of (30) people who were partially selected from (30) afflicted families in The monkey shelter center, in this state of emergency as a result of the family’s crack and collapse of their buildings to leave the country of origin and migrate to the shelter center. The sample consisted of (18) males and (12) females, and the sample consisted of (20) married people, and (10) unmarried people. Married. The results of the current study showed that (83.3%) of the sample members had a low level of death anxiety, (10%) had a medium level of death anxiety, and (6.7%) had a low level of death anxiety. It also showed that there were differences in death anxiety according to Rich status. Social (married, unmarried), communication between married couples, differences in death anxiety, specific date, gender (male, female)